A review of measured bioaccumulation data on terrestrial plants for organic chemicals: Metrics, variability, and the need for standardized measurement protocols. (8th December 2017) - Doucette, William J.; Shunthirasingham, Chubashini; Dettenmaier, Erik M.; Zaleski, Rosemary T.; Fantke, Peter; Arnot, Jon A.
Abstract: Quantifying the transfer of organic chemicals from the environment into terrestrial plants is essential for assessing human and ecological risks, using plants as environmental contamination biomonitors, and predicting phytoremediation effectiveness. Experimental data describing chemical uptake by plants are often expressed as ratios of chemical concentrations in the plant compartments of interest (e.g., leaves, shoots, roots, xylem sap) to those in the exposure medium (e.g., soil, soil porewater, hydroponic solution, air). These ratios are generally referred to as "bioconcentration factors" but have also been named for the specific plant compartment sampled, such as "root concentration factors, " "leaf concentration factors, " or "transpiration stream (xylem sap) concentrations factors." We reviewed over 350 articles to develop a database with 7049 entries of measured bioaccumulation data for 310 organic chemicals and 112 terrestrial plant species. Various experimental approaches have been used; therefore, interstudy comparisons and data‐quality evaluations are difficult. Key exposure and plant growth conditions were often missing, and units were often unclear or not reported. The lack of comparable high‐confidence data also limits model evaluation and development. Standard test protocols or, at a minimum, standard reporting guidelines for the measurement of plant uptake data are recommended to generate comparable, high‐quality data that will improve mechanistic understanding of organic chemical uptake by plants. Environ Toxicol Chem 2018;37:21–33. © 2017 SETAC